Promoting research through claiming centrality and explicit research contributions in applied linguistics research articles - Warsidi (JOALL (Journal of Applied Linguistics and Literature), 2023)
Since authors intend to publish their academic research in reputable journals, promoting their research significance is pivotal to convincing journal gatekeepers for accepting their research articles (RAs). However, studies on research promotion within RAs are still limited, and none has comparatively studied this essential issue in English RAs published in reputable international journals and Indonesian highly-accredited journals as data sets. Thus, comprehending this gap has encouraged me to conduct the present study, by analyzing how claiming centrality and research contribution are employed in both data sets. For the data analysis, I employed a top-down approach for analyzing both data sets and used combined qualitative and quantitative approaches for the analysis reports. Then, the analysis results revealed that while claiming centrality appeared in most of both data sets, presenting research contribution appeared only in a few RAs of both data sets. Then, authors tend to express these two communicative steps using simple sentences more than the other three sentence types, except those published in reputable international journals as they mostly employ complex sentences in expressing their research contribution. These findings imply that promoting research by stating that the current research topic is important for research is important in the data, but using claiming centrality is more dominant than presenting research contribution. These findings also indicate that promoting the significance of current research topics is very essential.